Engaging Nurses in Research for a Randomized Clinical Trial of a Behavioral Health Intervention. (11th September 2013) - Roll, Lona; Stegenga, Kristin; Hendricks-Ferguson, Verna; Barnes, Yvonne J.; Cherven, Brooke; Docherty, Sharron L.; Robb, Sheri L.; Haase, Joan E.
Abstract : Nurse involvement in research is essential to the expansion of nursing science and improved care for patients. The research participation challenges encountered by nurses providing direct care (direct care nurses) include balancing patient care demands with research, adjusting to fluctuating staff and patient volumes, working with interdisciplinary personnel, and feeling comfortable with their knowledge of the research process. The purpose of this paper is to describe efforts to engage nurses in research for the Stories and Music for Adolescent/Young Adult Resilience during Transplant (SMART) study. SMART was an NIH-funded, multisite, randomized, behavioral clinical trial of a music therapy intervention for adolescents/young adults (AYA) undergoing stem cell transplant for an oncology condition. The study was conducted at 8 sites by a large multidisciplinary team that included direct care nurses, advanced practice nurses, and nurse researchers, as well as board-certified music therapists, clinical research coordinators, and physicians. Efforts to include direct care nurses in the conduct of this study fostered mutual respect across disciplines in both academic and clinical settings.